Dinamika Persepsi Orang Tua dan Guru Terhadap Penggunaan Gawai dalam Pendidikan Disiplin Anak - Diana Lutfiana Ulfa; Lituh Sinana (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Nahdlatul Ulama Blitar, 2026)
This study aims to describe the similarities and differences between parents’ and teachers’ perceptions regarding the use of digital devices in children’s discipline education, as well as to analyze the role of Civic Education (PKn) as a framework for developing disciplined behavior in device use at home and at school. The research was conducted at SDN Mangunan 02, Blitar, using a qualitative approach through in-depth interviews, observation, and documentation. The findings indicate diverse perceptions of device use: some parents have provided their children with personal devices, while others restrict access by allowing the use of parents’ devices only. A similar dynamic appears among teachers: the use of devices at school remains limited due to the small number of Chromebooks available to be shared among classes, yet teachers still encourage digital engagement through online assignments. Furthermore, PKn values are shown to be an important framework in fostering discipline, responsibility, and self-control in children’s use of technology. This study highlights that synergy between parents’ and teachers’ perceptions and educational roles is essential to cultivating a healthy digital discipline culture among elementary school students.